The development of the term [enypostatos] from Origen to John of Damascus - Gleede, Benjamin. (Vigiliae Christianae, Supplements, 2012)
Examining the usage of the term ἐνυπόστατος both in the trinitarian debates before Chalcedon and especially the Christological ones afterwards, this study illustrates the gradual, yet profound change in its meaning initiated by Leontius of Byzantium: In distinguishing between the hypostasis and the ἐνυπόστατον Leontius initiates a crucial shift in that an ἐνυπόστατον is no longer straightforwardly considered as a proper, independent hypostasis of its own, but as something realized in a hypostasis which is by no means necessarily endowed with a hypostasis of its own. This technical discussion of the term is accompanied by an attempt at classifying the entirety of the different usages it keeps on displaying despite its Christian theological origin and its outstanding importance during the post-chalcedonian Christological debates.